Wiedza osobista dziecka w młodszym wieku szkolnym jako przestrzeń (nie)codziennych działań nauczyciela - Kochanowska, Ewa (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Children starting school education have already shaped some assortment of knowledge and experience acquired in the course of daily activities in their environment. The everyday school practice may include unconventional, non-stereotypical forms of a teacher’s didactic activities, which are different from those ordinary, used on daily basis practices and target at different areas ofa child’s functioning. Some of them relate to a schoolchild’s knowledge, especially to the ratio of a teacher’s attitude towards a child’s personal knowledge, values that are attributed to it in the educational process and the use of a child’s personalknowledge in the construction of school knowledge. Such activities include both, teaching situations consciously organized by a teacher as well as those spontaneously appearing in the learning process, aimed at activating and using personal knowledge of a child. The purpose of this paper is to show attitudes towards activation and use of a child’s personal knowledge in school practice typical of early school education teachers.
Keywords: codzienność; dydaktyka; dzieci; nauczyciel; szkoła; wiedza osobista